2017
DOI: 10.22159/ajpcr.2017.v10s5.23098
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Potential Drugs Interaction on Antihypertension Drugs Prescription in Community Health Center of Sukmajaya District in Period of June-November 2015

Abstract: Objectives: Hypertension is a common disease around the world. Depending on the severity or the presence of other diseases, whether related or unrelated, additional drug therapy may be required to optimize treatment and to reduce the side effects of drugs. The use of drugs in large amounts may increase the risk of drug interactions. The purpose of this research was to evaluate the characteristics of hypertension patients, prescriptions, and potential drug interactions in hypertensive patients in the Sukmajaya … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…This interaction can cause serious heart disease, such as ventricular arrhythmias and sudden cardiac death, which has been shown by cohort studies that found a link between serious ventricular arrhythmias and sudden cardiac death in the use of domperidone at dosages >30 mg/day in patients >60 years old. [ 14 ] To avoid this interaction, the lowest dosage and short duration of domperidone are recommended. If the patient experiences fainting, dizziness, palpitation, and seizures after receiving domperidone, it must be stopped.…”
Section: Discussionmentioning
confidence: 99%
“…This interaction can cause serious heart disease, such as ventricular arrhythmias and sudden cardiac death, which has been shown by cohort studies that found a link between serious ventricular arrhythmias and sudden cardiac death in the use of domperidone at dosages >30 mg/day in patients >60 years old. [ 14 ] To avoid this interaction, the lowest dosage and short duration of domperidone are recommended. If the patient experiences fainting, dizziness, palpitation, and seizures after receiving domperidone, it must be stopped.…”
Section: Discussionmentioning
confidence: 99%
“…Drug replacement is done by replacing the antibiotic with commonly given antibiotics such as amoxicillin or eliminating the use of anti-inflammatory drugs in patients during erythromycin use. In addition, health facilities should also file or collect data on interactions that occur as well as routine monitoring of all types of interactions [1,33].…”
Section: Potential Drug Interactionmentioning
confidence: 99%
“…In an attempt to normalize the blood pressure and glucose levels, multiple drugs may predispose the patient to polypharmacy [9] and have the potential to interact, thereby producing undesirable effects [10]. Studies have also indicated that about 60% of patients may have drug interactions that will cause undesirable outcomes.…”
Section: Introductionmentioning
confidence: 99%